Nasal endoscopic repair of cerebrospinal fluid rhinorrhea: case series of ten patients - Maqbool Ahmed Baloch; Sabah Kaleem Baloch; Sadaf Rashid (Gomal Journal of Medical Sciences, 2012)
Background: CSF rhinorrhea is a rare entity but it needs proper evaluation and management. Previously it was managed through intracranial approach carrying increased morbidity and mortality. Since the introduction of nasal endoscopic surgery in 1981, it is being managed through transnasal endoscopic technique which has high success rate and less morbidity. The purpose of this study was to review the clinical presentation, etiology, diagnosis and outcome of nasal endoscopic repair in CSF rhinorrhea.